Development of plasma and ion beam technology for material engineering at NCBJ - Nowakowska-Langier, K. (Вопросы атомной науки и техники, 2019)
The Plasma/Ion Beam Technology Division is one of several laboratories forming the Material Physics Department at the NCBJ in Świerk, Poland. Scientific activity of the Division concerns different aspects of research related to material engineering, surface engineering, functional properties characterization, as well as synthesis and modification of different materials.Plasma surface engineering methods like cathodic arc UHV deposition and pulsed magnetron sputtering methods as well as ion beam implantation methods are intensively exploited and developed in our laboratory.